Pemberdayaan Ekonomi Pemuda Pengangguran Terdampak Covid-19 dalam Berwirausaha Melalui One Person One Product (OPOP) Berbasis Agroindustri Tahu di Kabupaten Jember - Tapaningsih, Weni Indah Doktri Agus (Proceedings of Annual Conference on Community Engagement, 2022)
The current economic development is greatly influenced by the Covid-19 situation. Many sectors of life have been disrupted due to the Covid-19 pandemic. This uncertainty situation resulted many of business actors laying off their workers, and causing a lot of unemployment. Jember Regency, which is one of the cities in East Java, also experienced this situation. The economic stimulation is needed through empowerment for young men unemployed who have been affected by Covid-19 pandemic. This community engagement based on empowering the young men community, especially for young men unemployed to become home busines entrepreneursman based on tofu products trough One Person One Product (OPOP) in Jember Kidul Village, Kaliwates District, Jember Regency. This activity based on the Asset Based Community Development (ABCD) method by using understanding and internalizing assets, potential, strength, and utilization with independently and maximallity. This activity received high appreciation from the local youngmen community, especially for young men unemployed who can help them to become youngentrepreneurs.